2014
DOI: 10.2337/dc14-0195
|View full text |Cite
|
Sign up to set email alerts
|

Roux-en-Y Gastric Bypass Surgery, but Not Calorie Restriction, Reduces Plasma Branched-Chain Amino Acids in Obese Women Independent of Weight Loss or the Presence of Type 2 Diabetes

Abstract: OBJECTIVEObesity and type 2 diabetes mellitus (T2DM) have been associated with increased levels of circulating branched-chain amino acids (BCAAs) that may be involved in the pathogenesis of insulin resistance. However, weight loss has not been consistently associated with the reduction of BCAA levels. RESEARCH DESIGN AND METHODSWe included 30 obese normal glucose-tolerant (NGT) subjects, 32 obese subjects with T2DM, and 12 lean female subjects. Obese subjects underwent either a restrictive procedure (gastric b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 22 publications
12
58
0
Order By: Relevance
“…Improving insulin sensitivity may also ameliorate BCAA metabolism, resulting in reduced diabetes risk. This approach is supported by the well-described reduction of amino acid levels following the administration or secretion of insulin [63,64], by our finding of higher BCAA levels in individuals with a genetic predisposition to insulin resistance, and by the observation of reduced BCAA levels following insulin-sensitising interventions [6567]. …”
Section: Discussionmentioning
confidence: 78%
“…Improving insulin sensitivity may also ameliorate BCAA metabolism, resulting in reduced diabetes risk. This approach is supported by the well-described reduction of amino acid levels following the administration or secretion of insulin [63,64], by our finding of higher BCAA levels in individuals with a genetic predisposition to insulin resistance, and by the observation of reduced BCAA levels following insulin-sensitising interventions [6567]. …”
Section: Discussionmentioning
confidence: 78%
“…These findings suggest BCAAs or their metabolites may contribute to non-weight loss improvements in insulin sensitivity and glucose metabolism (Laferrere et al, 2011). The RYGB specific reduction in BCAAs has been confirmed when compared with AGB and very low calorie diet induced weight loss (Lips et al, 2014). However, in another well conducted study, RYGB and AGB were found to cause the same reduction in circulating BCAAs and their metabolites (Magkos et al, 2013).…”
Section: Branched-chain Amino Acidsmentioning
confidence: 85%
“…BCAA deprivation in rodents also improves insulin sensitivity in insulin resistant mice [13]. On the other hand, the rapid increase in insulin sensitivity and improvement in glucose homeostasis following weight loss surgery coincides with reductions in circulating BCAA, AAA, and several AA metabolites [1416]. In addition, three months of metformin monotherapy has been reported to reduce AAA in patients with T2D [17].…”
Section: Introductionmentioning
confidence: 99%